Exploring the possibilities of steel-fiber reinforced self-compacting concrete for the flexural strengthening of masonry structural elements - Häßler, D. (2013)
The potentialities of a thin layer of steel fibre reinforced self-compacting concrete (SFRSCC) for the flexural strengthening of handmade brick structural elements are investigated. For this purpose an experimental program was carried out covering the relevant phenomena that can influence the effectiveness of this technique. The SFRSCC has a post-cracking residual tensile strength capable of improving the flexural stiffness, flexural resistance and ductility of prototypes representatives of ancient handmade brick based structures that fail in bending. To appraise the flexural strengthening effectiveness of this technique, straight beams composed of handmade bricks, low strength mortar (LSM) and SFRSCC were tested. The obtained results have shown that this technique can increase significantly the flexural stiffness and resistance, and the ductility performance of 2 this type of structures. The strengthening effectiveness depends on the post-cracking residual strength of the SFRSCC, its layer thickness and on the possibility of replacing part of the LSM by SFRSCC. Based on the experimental results for the characterization of the intervening materials, and adopting a cross section layer model capable of predicting the moment-curvature relationship for the distinct types of cross sections of this structural system, the maximum load registered in the tested prototypes was predicted with good accuracy.